2022
DOI: 10.3389/fpsyt.2021.822579
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Potential Role in Systemic Inflammation and Negative Symptoms After Acute Antipsychotic Treatment in Schizophrenia

Abstract: Uric acid (UA) has been shown to have neuroprotective or neurotoxic properties, in relation to specific tissues and diseases that have been studied. Previous studies provided contradictory results on the role of UA in schizophrenia as a neurodegenerative disorder. The aim of this brief report was an additional analysis of UA sera levels in different phases of schizophrenia. Here, 86 patients with first-episode psychosis (FEP) vs. 45 patients with schizophrenia in relapse (SC in relapse) vs. 35 healthy control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The reduction in UA levels has been previously confirmed to be a marker of abnormal antioxidant defense systems in patients with SCZ (48). Indeed, this was the case given that UA levels are significantly lower in patients with SCZ than in healthy controls (31,49,50). Uric acid levels have been associated with negative symptoms after treatment in patients with SCZ in the acute phase (51) and negatively associated with symptom severity (52).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The reduction in UA levels has been previously confirmed to be a marker of abnormal antioxidant defense systems in patients with SCZ (48). Indeed, this was the case given that UA levels are significantly lower in patients with SCZ than in healthy controls (31,49,50). Uric acid levels have been associated with negative symptoms after treatment in patients with SCZ in the acute phase (51) and negatively associated with symptom severity (52).…”
Section: Discussionmentioning
confidence: 88%
“…Uric acid levels have been associated with negative symptoms after treatment in patients with SCZ in the acute phase ( 51 ) and negatively associated with symptom severity ( 52 ). Studies on UA and cognitive impairment (one of the three major symptoms of SCZ and the main barrier to SCZ rehabilitation) in patients with SCZ have only been conducted on first-episode, drug-free populations and found no statistically significant associations ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous studies have shown that oxidative stress and neuroinflammation are significantly associated with psychiatric disorders such as depression, anxiety, and schizophrenia. 31 , 32 There is a lack of studies on the association between UA and inflammation and oxidative stress in this study, so it is necessary to actively explore the correlation between cognitive impairment or UA level and inflammation and oxidative stress in future studies. In conclusion, the occurrence of cognitive impairment caused by alcohol dependence is closely related to the increase of serum UA levels in alcohol-dependent patients.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is supported by the fact that disseminated activation of microglial cells is the primary characteristic of the chronic phase of the illness[ 44 ]. There is ample evidence of biomarkers indicating a link between immunological processes, psychotic disorders and MS. Elevated levels of different inflammatory markers have been found in the blood and cerebrospinal fluid (CSF) of patients with psychosis and MS, with particularly high levels in patients with first-episode psychosis or acute relapse[ 45 , 46 ]. Dysregulation of regulatory T cells and Th17 cells may be essential for immunological homeostasis and play a role in the development of both diseases[ 47 , 48 ].…”
Section: Neuroimmunological Aspects Of Ms and Psychosismentioning
confidence: 99%